SUATU PARADOKS DALAM PEMBANGUNAN EKONOMI TERHADAP PENGANGGGURAN DAN KEMISKINAN - Rosmiyati Chodijah (Department of Development Economics, Universitas Sriwijaya, 2010)
Indonesia's development shows optimism, in the economic field is indicated by the macro indicators, but donot automatically solve basic human problems that is the problem of poverty and unemployment. Governments need to run the policy for the real sector with availabilityÂ Â of investment requirements in support of Bill worthy investment to appreciate, and be able to develop a level playing field. The real sector has the challenge of complex micro scale (called UMKMK). Technology andÂ Knowledge based Economy-TKBE is an economic system design to achieve prosperity by improving growth and competitiveness. The role of microfinance institutions and government partisanship on small business is expected to be the key to Indonesia's economic revival. Alternative development approach has become mainstream economic thought, through the paradigm of equity will create a strong foundation for sustainable economic growth. In the end, the fundamental problem is how to develop the economy based on cultural pluralism and diverse resources of the nation, an adjustment strategy to find the identity of the nation, amid a leap of technological progress that close the gap and time and the boundaries between countries are artificial things. Keywords: Poverty, UnempolymentMonetary expansion, Aggregate Demand